(untitled) (International Journal of Physiotherapy, 2016)
Background: Proprioceptive deficiency followed by lateral ankle sprain leads to poor balance is not uncommon. It has been linked with increased injury risk among young athletes. Introducing neuromuscular training programs for this have been believed as one of the means of injury prevention. Hence, this study was aimed to determine the effects of six weeks progressive neuromuscular training (PNM Training) on static balance gains among the young athletes with a previous history of ankle sprains. Methods: This study was an experimental study design, with pre and post test method to determine the effects of PNM Training on static balance gains. All data were collected at university’s sports rehabilitation lab before and after six weeks of intervention period. There were 20 male and female volunteer young athletes (20.9 ± 0.85 years of age) with a previous history of ankle sprain involving various sports were recruited from the University community. All the subjects were participated in a six week PNM Training that included stability, strength and power training. Outcome measures were collected by calculating the errors on balance error scoring system made by the athletes on static balance before and after the six weeks of intervention period. Static balance was tested in firm and foam surfaces and recorded accordingly. Results: The researchers found a significant decrease (2.40 ± 0.82) in total errors among the samples at the post test compared with their pre test (P >0.05). Conclusions: The study demonstrates that a PNM Training can improve the static balance on both the firm and foam surfaces among the young athletes with a previous history of ankle sprains.